Molecular and cellular features of anteromedial gonarthrosis - Rout, R (2012)
Anteromedial Gonarthrosis (AMG) is a distinct phenotype of knee osteoarthritis (OA), with a specific pattern of disease on the tibia. There is full thickness cartilage loss anteromedially, progressing to an area of damaged cartilage, and then to an area of macroscopically and histologically normal cartilage posteriorly. This reproducible pattern of disease can be considered to be a spatial model of OA progression and provides an alternative and less biologically varied set of specimens than the commonly used multiple joint compartments in which to quantify disease-related changes. The aim of this thesis was to explore in detail spatial and quantitative differences in cell, matrix and molecular features between areas of cartilage in AMG. A real time PCR study was undertaken comparing damaged and undamaged cartilage in AMG. Previous work from our research group had shown increased type I collagen content of undamaged cartilage in AMG. This gene expression study corroborated this finding by demonstrating increased COL1A1 expression in undamaged cartilage, compared to damaged cartilage. MMP1, MMP3, MMP13 and ADAMTS4 were also shown to have increased expression in undamaged cartilage. Since these changes arise in tissue before any macroscopic damage is apparent, these may indicate early changes of the cartilage matrix in AMG. In order to confirm that these changes are directly related to the damage process and not only to normal regional variations, Above Knee Amputations were collected from patients with peripheral vascular disease but no overt OA and a template of the AMG joint surface created to allow for matched regional sampling. Studies into their histology, immunoassays and qPCR were performed in order to compare results with those from AMG specimens. Histology demonstrated low scores throughout but allowed for a division into lower (macroscopically and histologically normal) and higher grade (surface wear/possible early signs of OA) groups. Immunoassays showed elevated type I collagen in high grade but not low grade groups in the posterior cartilage. No differences in mRNA expression were detected using qPCR suggesting that changes seen in AMG specimens were specific to the OA disease process. Because the causes of cell death in OA are not fully understood an immunohistochemical study into apoptosis was performed. TUNEL staining demonstrated higher levels of apoptosis, the more damaged the cartilage. The presence of Active Caspase 3, Cytochrome C, Active Bax and Bim with the same distributions demonstrated apoptosis occurring via the intrinsic or mitochondrial pathway. The high levels of 3-Nitrotyosine in more damaged cartilage implicated reactive oxygen species in apoptotic mechanisms. A microarray study was conducted comparing regions of damaged and undamaged cartilage in AMG. 389 genes were found to be significantly differentially expressed between regions. Several pathways rich in gene expression changes were highlighted including cellular development, inflammatory response and skeletal disorders. Results suggest complex changes in the signaling microenvironment of AMG and identify areas for future study. In summary, this thesis has highlighted several quantitative molecular and cellular differences between regions of cartilage in AMG, demonstrating its usefulness as a tight disease model. Gene expression differences corroborate changes previously seen by immunohistochemistry; microarray has shown the wider picture of gene expression changes. Apoptosis has been shown to occur via the intrinsic pathway and involve reactive oxygen species, highlighting this damage pathway as an important driver of cell loss. Most importantly this thesis has identified the apparently normal region in AMG specimens as a region undergoing considerable molecular changes and as a potential early disease model. The dysregulation of collagen I distribution seen in AMG and slightly worn AKA specimens is very interesting and suggests a possible early response to loading alterations caused by joint wear and opening the way for future experiments. The identification of wear patterns in AKA specimens specifically mapping to the zone of maximal damage in AMG confirms the site of initial injury and progression over time proposed in this model. These AKA specimens with no overt OA should therefore be used in future studies to assess emerging biomarkers of disease progression.